The Influence Of Esg Risk Rating On Company Value In Companies Listed On Stock Exchanges Collaborating In ASEAN-ISE - Moh. Baqir Ainun; Liyanto Liyanto (UNIVED Press, 2025)
This study aims to examine the effect of ESG risk rating on company value in companies listed on the ASEAN-ISE member stock exchanges. The research sample is companies listed on the Stock Exchange that are members of ASEAN-ISE, namely Bursa Malaysia Berhad (Bursa Malaysia), Indonesia Stock Exchange (IDX), Stock Exchange of Thailand (SET), and Singapore Exchange (SGX Group) in 2023 as many as 101 observations. This study uses a new approach in measuring ESG, namely using the company's ESG Risk Rating which has combined three ESG concepts (environmental, social, and governance). In addition, the sampling is expanded to cross-country will expand the generalization of the research results and is also a novelty in this study. The data analysis used is multiple linear regression. The results of the study show that ESG risk rating has a negative effect on company value, but not significant. This study can add to the literature on ESG and company value, and can provide important information that there is an ESG risk rating that has not been optimally utilized in the decision-making process.